El fraude informático en España e Italia. Tratamiento jurídico-penal y criminológico (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This article aspires to give a general penal and criminological legal perspective of the most relevant aspects of the computer fraud in Spain and Italy. It emphasizes the differences and similarities between both legislations. And it describes the criminological aspects in a general and simultaneous approach as the same aspects exist inboth countries.
Keywords: Swindling; computer fraud; criminal law; criminology; Spain; Italy.